Effect of pyrolysis temperature on the yield and properties of bio-oils obtained from the auger pyrolysis of Douglas Fir wood - Liaw, S.; Wang, Z.; Ndegwa, P.; Frear, C.; Ha, S.; Li, Chun-Zhu; Garcia-Perez, M. (Elsevier, 2012)
This paper reports the effect of pyrolysis temperature on the yield and composition of bio-oils obtained from the auger pyrolysis of Douglas Fir wood. The tests were conducted at reactor wall temperatures between 200 and 600 °C. Due to the relatively low heat transfer rates achieved between the reactor wall and the biomass particles, the temperature of the solid residue obtained was much lower (between 117 and 420 °C). Bio-oil yields were close (maximum yield: 59 mass%) to those reported for fluidized bed reactors (more than 60 mass%). The maximum oil yield was obtained at a reactor wall temperature of 500 °C (biomass residue heated up to 328 °C). At this temperature, maximum yields of Douglas Fir primary degradation products (lignin oligomers, anhydrosugars, 2-furaldehyde, 2(5H)-furanone, 2-furanmethanol, β-methoxy-(S)- and alkylated and methoxylated phenols) were observed. The yield of products from secondary thermochemical reactions (phenol; phenol, 4-ethyl, O-cresol; phenol, 3,4-dimethyl; cresol; pyrotechol, and phenol 2,4-dimethyl, methanol and gases) increased with temperature. In all cases, the yield of the products from secondary reactions was higher than those reported for fluidized bed reactors at comparable temperatures. The water yield (11 mass%) obtained with the auger reactor was comparable to those reported for other materials processed in fluidized bed reactors. The results obtained confirm that the auger reactor is able to achieve good yields of both bio-oil and bio-char but that the overall composition of the oil obtained will be affected by the slower heating rates achieved and the intensification of secondary reactions in gas phase.